Developing an Effective Conceptual Framework for Safety Behaviour in Construction Industry - Zid, Chaher; Narimah, Kasim; Benseghir, Hocine; Kabir, M. Nomani; Abdullah, Ibrahim (EDP Sciences, 2018)
The construction industry involves one of the most hazardous occupation for workers due to complex management processes, environmental issues, work pressure and heavy and complicated equipment involved in modern construction projects. Despite the advancement of technology in the construction industry, an escalating number of fatal accidents occur because of the human errors and the unsafe behaviours. In this research, an analysis for previous studies has been conducted to define all safety behavioural factors in construction industry for improving the safety performance in construction industry. All the studies were categorised in accordance with their methodologies, analytical methods, variables, and the findings in order to build an effective conceptual framework. The framework comprises of three main categories that incur direct impact toward the safety behaviour in construction industries, namely: (a) organizational factors, (b) safety climate factors, and (c) individual factors. Each category has own variables which make a total of 16 factors for all categories. The framework facilitates to assess the effectiveness of a construction industry, identify the deficiencies and the weakness, and create procedures to manage the accident in future by controlling the safety behaviour of employees.